The Use of Medicinal Plants in Chronic Cholecystitis - Nurova Nigora Sadilloyevna (American Journal of Bioscience and Clinical Integrity, 2024)
Chronic cholecystitis is an important medical and socio-economic problem of modern society. Over the past decade, both domestically and internationally, despite advancements in therapy with the introduction of new effective agents for treating functional disorders of the digestive system, there has been a notable rise in the occurrence of biliary system ailments. The pathologies concerning the biliary tract and pancreas pose significant challenges to contemporary medicine, with this trend showing stability.